The Utilization of Bacillus spp. as Endophytes in Enhancing Plant Resistance and Health Against Fusarium oxysporum : A Mini Review - Rumandani, Nabila Auriza; Salamun, Salamun; Hamidah, Hamidah (Syntax Literate, 2025)
Fusarium oxysporum is a destructive pathogen responsible for significant losses in chili (Capsicum spp.) and other crops. Traditional chemical control methods pose environmental and health risks, highlighting the need for sustainable alternatives. This review explores the role of Bacillus spp. as endophytic biocontrol agents in combating F. oxysporum. Species such as B. subtilis, B. mojavensis, and B. velezensis exhibit antifungal activity through the production of hydrolytic enzymes (e.g., glucanase, cellulase, and chitinase) and secondary metabolites like lipopeptides and antibiotics, which inhibit pathogen growth. Furthermore, these bacteria enhance plant health by inducing systemic resistance, promoting root development, and creating a rhizosphere environment unfavorable to pathogens. Their synergistic interactions with other beneficial microorganisms further bolster plant defense and productivity. Molecular and physiological analyses confirm the efficacy of Bacillus spp. in reducing disease severity and improving plant resilience. Continued research into their mechanisms and field application can support more sustainable agricultural practices.